PERAN TRANSFORMASI DIGITAL DALAM MENDUKUNG BISNIS UMKM MELALUI PLATFORM PEMBAYARAN QRIS MIKHA SHOP PALU - Yuly Azahra; Erwinsyah; Phatra Anggana Djuri; Femilia Zahra (Publika Citra Media, 2025)
This study aims to examine the impact of implementing the Quick Response Code Indonesian Standard (QRIS) in supporting digital transformation among micro, small, and medium enterprises (MSMEs), with a case study at Toko Mikha Shop in Palu City. The research employed a qualitative approach through in-depth interviews, observations, and document analysis, complemented by descriptive quantitative data. The findings reveal a significant shift in transaction patterns after the adoption of QRIS, where digital payments accounted for 50% of total transactions, compared to previously 100% cash payments. Furthermore, the shop’s monthly sales turnover increased by 20%, rising from IDR 15,000,000 to IDR 18,000,000. QRIS was found to simplify payment processes, accelerate transactions, enhance operational efficiency, and support more accurate and organized financial record-keeping. Its implementation also contributed to improved customer satisfaction. However, challenges such as a 0.7% transaction administration fee, delays in fund disbursement, and unstable internet connectivity remain critical issues. This study recommends enhancing digital literacy among MSME actors, improving technological infrastructure, and providing supportive policies to optimize the sustainable use of QRIS